Okužba s pripravki CCB zaščitenih izpranih lesnih vzorcev z glivami - Humar, Miha (Zbornik gozdarstva in lesarstva, 2003)
CCB treated wood is generally resistant to all wood decay fungi. However, like at CCA impregnated wood, susceptibility of CCB treated wood to copper tolerant fungi have been observed. It was investigated whether the hyphae of brown rot fungi could overgrow on and penetrate into the wood samples. Samples made of Norway spruce (Picea abies) were impregnated with 5 % CCB solution according to the EN 113 procedure. After conditioning, part of the samples was leached according to the EN 84 method. A small stick of unimpregnated wood (r = 1.5 mm, l = 25 mm) was inserted into a hole, bored in the center of the sample, and then sealed with epoxy coating. Sterilized, leached and non-leached impregnated and unimpregnated specimens were exposed to two copper-tolerant (Antrodia vaillantii, Leucogyrophana pinastri) and two copper sensitive (Poria monticola, Gloeophyllum trabeum) brown rot fungal strains. After exposure, the inserted wood pieces were removed from the specimens and put onto nutrient medium in petri dishes. Growth of the hyphae from those wood pieces was then visually determined. Rate of colonization by the fungi was determined by measurement of CO2. Mass losses after 16 weeks of exposure were also determined. The fastest colonization of the unimpregnated specimens was by G. trabeum. On the other hand, no fungal growth could be detected on non-leached CCB impregnated specimens even after 12 weeks of exposure. However, significantly more intense colonization by the copper tolerant fungi was detected on the leached CCB treated samples. We concluded that the reason for observed higher susceptibility originates in leached boron, which did not influence, in lower concentrations, fungal growth.
Keywords: bakrove spojine; glive; les; razkroj; vplivi